If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 28 + -1 + 10 = x + -1 Combine like terms: 28 + -1 = 27 27 + 10 = x + -1 Combine like terms: 27 + 10 = 37 37 = x + -1 Reorder the terms: 37 = -1 + x Solving 37 = -1 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 37 + -1x = -1 + x + -1x Combine like terms: x + -1x = 0 37 + -1x = -1 + 0 37 + -1x = -1 Add '-37' to each side of the equation. 37 + -37 + -1x = -1 + -37 Combine like terms: 37 + -37 = 0 0 + -1x = -1 + -37 -1x = -1 + -37 Combine like terms: -1 + -37 = -38 -1x = -38 Divide each side by '-1'. x = 38 Simplifying x = 38
| ln(40)-2ln(5)=0 | | 9z+29x=8x-13 | | 34-3x=16 | | -19+x-2=11-19+9 | | 4x+7=20(3-2x)+7 | | 17-8+x=8+7-3 | | -23+(-45)= | | 0.2x+9.7=8.4 | | 3(x+5)=6x+8 | | 8(x-8)=24-3x | | 20+5x+4x-11=180 | | 9(2)+3y=4y-9(4) | | (1/2)(6x-8)=(7/5)(x-5)-(1/5) | | 1x+25=-3 | | -6=x+100 | | 2x+x=359 | | 60=-w+176 | | 36-x=267 | | 158=239-u | | 1(15x)+25=-3 | | 245=-u+123 | | 7/2=3/2n-7/2n | | 5-4x=4x-5-4x-2 | | 8+8x=14+8x | | 14-(3a+2)= | | 1.4=log(x) | | 7z+5-2z=47-2z | | 7x-2(2x-1)=17 | | 25-(25x)=22 | | 25-(25x)=10 | | 4(w+3)=8(w-1) | | X^4-13x^2+36=(x-3) |